Electron emission from clean metal surfaces induced by low-energy light ions. - Baragiola, R. A.; Alonso, E. V.; Oliva-Florio, A. (American Chemical Society's, 1979)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina